Impurity-impurity pair correlation function and paramagnetic-to-ferromagnetic transition in the random Ising model - Ivaneyko, D.; Berche, B.; Holovatch, Yu.; Ilnytskyi, Ja. (Вопросы атомной науки и техники, 2007)
In this Monte Carlo study we concentrated on the influence of non-magnetic impurities arranged as the lines with random orientation on paramagnetic-to-ferromagnetic phase transition in the 3D Ising model. Special emphasize is given to the long-distance decay of the impurity-impurity pair correlation function. It is shown that for the lattice sizes considered (L=10-96) and for the two different impurity distributions (purely random and mutually avoiding lines) the function is governed by the power law of 1/ra with an universal exponent a≈2. This result supports our findings about the numerical values of the critical exponents governing magnetic phase transition in the 3D Ising model with long-range-correlated disorder. Oбговорюються результати досліджень методом Монте-Карло впливу немагнітних домішок у вигляді ліній з випадковою орієнтацією на фазовий перехід парамагнетик-феромагнетик в тривимірній моделі Ізинга. Особливу увагу приділено загасанню на великих відстанях парної кореляційної функції домішка-домішка. Для розглянених розмірів граток (L=10…96) і для двох типів розподілу домішків (лінії, що перетинаються і лінії, що не перетинаються) показано, що функція має степеневий вигляд 1/ra з універсальним показником a≈2. Цей результат підтверджує отримані нами числові значення критичних показників магнітного фазового переходу в тривимірній моделі Ізинга з далекосяжно-cкорельованим безладом. Oбсуждаются результаты исcледований методом Монте-Карло влияния немагнитных примесей в виде линий со случайной ориентацией на фазовый переход парамагнетик-ферромагнетик в трехмерной модели Изинга. Особое внимание уделено угасанию на больших расстояниях парной корреляционной функции примесь-примесь. Для обсуждаемых размеров решеток (L=10…96) и для двух типов распределений примесей (пересекающиеся и непересекающиеся линии) показано, что функция подчиняется закону 1/ra с универсальным показателем a≈2. Этот результат поддерживает полученные нами ранее данные о числовых значениях критических показателей магнитного фазового перехода в трехмерной модели Изинга со скоррелированным на больших расстояниях беспорядком.